Study and distribuition of rabies virus in non neuronal organs in bats sent to laboratory diagnosis in Pasteur Institute (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The diversity of bat species in Brazil is great, and there are 172 species distributed among nine families. The Phyllostomidae family is the most numerous, followed by Vespertilionidae and Molossidae. According to feeding habits, the majority of bats are insectivorous, followed by frugivorous, nectarivorous, carnivorous and hematophagous. As these animals are considered reservoirs of rabies virus it is essential to correctly identify the species and knowledge of the c rmv s p . g o v . b r mv&z 79 biology, behavior and adaptation of bats in urban environments. The objective of this study was to identify the several specimens of bats received for rabies diagnosis at the Pasteur Institute, meet the positive index of them and assess their distribution on the feeding habits in relation to the seasons. In the period between January and December 2011, specimens of bats were received for the rabies diagnosis and submitted to identificate the family, genus and/or species, according to identification keys, journals and scientific books. We also recorded the feeding habits and month of capture of animals. The period of this study was divided according to the seasons. During this period, 2846 specimens of bats were identified, being 77.6%,11.4% and 11% belonging to the Molossidae, Vespertilionidae and Phyllostomidae families, respectively. Of the total of bats identified 88.53% had habits insectivorous, 6.82% frugivorous, 4.39% sucking nectar and 0.28% hematophagous. In the warmer seasons of the year (spring and summer) it was received 1808 bats being 1727 insectivorous, 48 frugivorous, 29 sucking nectar and two hematophagous. In the colder seasons (autumn and winter), it was received 1038 bats being divided into 791 insectivorous, 145 frugivorous, 95 sucking nectar and 6 hematophagous. In relation to the rabies diagnosis, 37 specimens (1.3%) were diagnosed as positive, including the families Vespertilionidae (17), Phyllostomidae (13) and Molossidae (7). According to feeding habits bats were classified into 30 insectivorous and seven frugivorous specimens. The positive rate in the winter, were four insectivorous and one frugivorous, and it seems smaller than other stations.The positive rate in the summer was higher in Vespertilionidae than in Molossidae. This result was different that was observed by Constantine in the USA. He observed the higher rate positive in Molossidae. The differences observed in this study suggested the importance of feeding habits and breeding season of bats, considering principally the supply of food and warm seasons. The knowledge of bats and seasonal identification studies can contribute to improve the epidemiological surveillance program used in rabies management in determining the existence of bats of different families and/or feeding habits in different seasons.